(untitled) (Journal of Business and Technology (Dhaka), 2016)
This research is conducted to identify the benefits that customers receive as a result of maintaining long-term relation with commercial banks. Necessary data were collected from 262 respondents of different commercial banks of Khulna city of Bangladesh. Multiple regressions with SPSS were applied for data analysis. Customers relational benefits can be categorized into three distinct benefit types: confidence, social and special treatment benefits. The results have showed that confidence benefit is the most pronounced factor for customers of banks. The findings have also revealed that confidence benefits and social benefits have statistically significant effect on customers retention which is the key building block of developing banking industry in Bangladesh. Journal of Business and Technology (Dhaka) Vol.10(1) 2015; 55-71